EFEKTIFITAS KOMBINASI FORMULA OIL CRAB DAN EKSTRAK DAUN KARAMUNTING (Melastoma malabathricum) PADA PROSES PEMATANGAN OVARI INDUK KEPITING BAKAU (Scylla sp.) - Iromo, Heppi; Maulianawati, Diana; Muhlis, Muhammad (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2023)
Mud crab are one of the fisheries commodities that have important economic value. Today the demand for mud crab on the market is increasing, so that the capture of mud crab is also increasing. To overcome this, various efforts have been made to meet market demand, namely by conducting seeding, fattening and enlargement of mud crab in the pond. This study aims to determine the maturity level of mud crab ovaries (Scylla sp.) by administering a combination of karamunting (M. malabathricum) leaf extract and thyroxine hormone. This study used a complete randomized design with 4 treatments and 3 replications. The treatments in this study were treatment A (control), treatment B (M. Malabathricum 0.25 mg/g and thyroxine hormone 0.1 µg/g), treatment C (M. Malabathricum 0.5 mg/g and thyroxine hormone 0.1 µg/g), treatment D (M. Malabathricum 1 mg/g and thyroxine hormone 0.1 µg/g). The results showed that the administration of a combination of karamunting leaf extract (M. malabathricum) and the thyroxine hormone in treatments B and C can accelerate the process of egg removal (berried), which is within 20 days. The combination of karamunting leaf extract (M. malabathricum) and the thyroxine hormone can accelerate the ripening ovaries of mud crab from control treatment.